Pemberdayaan Masyarakat Melalui Pemanfaatan Jerami Jagung Sebagai Pakan Ternak Di Desa Leu Kecamatan Bolo Kabupaten Bima - Oscar Yanuarianto; Mastur Mastur; Intan Putri Mantika; Ica Ayu Wandira; Burhan Burhan (Universitas Mataram, 2020)
Currently, corn has become one of the leading commodities. This commodity can replace traditional crops such as green beans and soybeans which have a high risk of failure and require extra care. On the other hand, the use of corn waste products such as corn stover as animal feed is an efficient effort to meet feed needs, which in turn increases farmers' income and reduces the problem of environmental pollution due to corn straw waste. Leu village is one of the corn plant cultivation centers in Bima Regency, therefore, it is very necessary to improve the community's ability to utilize corn straw as animal feed; one of them is through community empowerment service activities that we have done. Community empowerment activities were attended by more than 20 participants including farmers, village officials, and extension office staff. Extension activities are carried out through demonstrations, orations (extracurricular lectures and discussions), and leaflet distribution. The results of community empowerment service activities were felt to be very useful; this was shown by the enthusiasm of the extension participants who were present during the activity